Effect of three breakfast interventions on blood glucose during low-intensity exercise performed on a treadmill - Paula Guedes Cocate; João Carlos Bouzas Marins (Universidade Federal de Santa Catarina, 2007)
The objective of this work was to evaluate blood glucose (BG) response during a low-intensity activity, preceded by the consumption of three different types of breakfast (BF). Fifteen Physical Education male students of mean age of 22.7 ± 2 years were evaluated. Three BF interventions were carried out on different days :fasting; BF1: cookie, juice, apple, cereal bar or BF2: 400 mL carbohydrate drink) 60 minutes before jogging/walking for 1 hour at 50-60% of maximum calculated HR (heart rate). Measurements of BG were taken at 60 and 30 minutes prior to activity and every 20 minutes during exercise. Heart rate, blood pressure (BP) and RPE were also monitored. Statistical analysis was by ANOVA with Tukey test and aimed to identify differences both in effect over time and between different BF interventions, to a signifi cance level of P < 0.05. The results indicate an absence of any difference in HR, BP or RPE response between the three procedures. There was a statistical difference in BG between BF1 and BF2 during the period immediately before exercise, but no differences were observed during exercise for any of the three treatments. In terms of behavior over time, BG at 30 minutes pre-exercise was signifi cantly higher than at other sample times, for both for BF1 and BF2. It was concluded that fasting or the levels of energy intake proposed in this study one hour before physical work did not cause alterations to the physiological responses of HR, RPE, BP or BG during that exercise activity. RESUMO O objetivo deste trabalho foi avaliar a resposta da glicose sangüínea (GS) ao longo de uma atividade de baixa intensidade, precedida pelo consumo de diferentes tipos de café da manhã (CM). Foram avaliados 15 estudantes Educação Física, do gênero masculino com idade média de 22,7 ± 2 anos. Os avaliados realizaram, em dias diferenciados, três ações de CM (CM0: jejum; CM1: biscoito, suco, maçã, barra de cereal; ou CM2: 400mL de bebida carboidratada) 60 minutos antes de um trote/caminhada a 50 - 60% da FC máxima calculada com duração de uma hora. A mensuração da GS ocorreu 60 e 30 minutos antes da atividade e durante intervalos de 20 minutos no exercício. Foram também monitorizadas a FC, pressão arterial (PA) e IPE. O tratamento estatístico correspondeu à ANOVA associada ao teste de Tukey, para determinar a existência de diferenças tanto no efeito tempo como entre as ações de CM, com nível de signifi cância de P < 0,05. Os resultados indicaram ausência de diferença na resposta da FC, PA e IPE entre os três procedimentos. A GS apresentou diferença estatística entre o CM1 e o CM2 no período imediatamente antes do exercício, porém sem diferenças durante o exercício para os três tratamentos. Quanto ao comportamento temporal, a GS aos 30 minutos pré-exercício, para CM1 e CM2, foi signifi cativamente mais elevada, comparada às demais parciais. Conclui-se que o jejum ou o consumo energético proposto neste estudo, uma hora antes do trabalho físico, não provocam alterações nas respostas fi siológicas da FC, IPE, PA e GS durante a atividade.